Fertility Does Not Alter Disease Progression in ALS Patients of Childbearing Age: A Three Centers Retrospective Analysis in Southern China - Yang, Biying; Huang, Sen; Zheng, Yu; Hou, Xiaomei; Lin, Jianing; Peng, Yu; Du, Baoxin; Yao, Xiaoli (Frontiers in Neurology, 2022)
Background: Limited data exists on the clinical features of patients with amyotrophic lateral sclerosis (ALS) during reproductive ages. Objective: Our study characterized the clinical features of ALS and the effects of pregnancy on disease progression in patients with ALS. Methods: We performed a retrospective study of female patients with ALS in three ALS research centers in southern China from 2009 to 2021. Data regarding fertility status, and clinical and genetic features, were collected. Age-matched male patients with ALS served as controls. The patients were divided into the following two subgroups: patients with symptom onset within 1 year of pregnancy and patients with symptom onset over 1 year group after pregnancy. Results: A total of 52 female and 52 matched male patients were enrolled. There were no differences in female and male patients in the mean age of symptom onset, the mean baseline ALSFRS-R score, or median reduction of ALSFRS-R score (p＞0.05). The mean age of first pregnancy was (25.57  4.40) years. The mean age of first pregnancy in the over 1 year group was lower than that in the within 1 year group (p= 0.01). There was no difference in the median reduction of ALSFRS-R between the two subgroups. In the univariate analysis, diagnostic delay was highly correlated with the disease progression, with short delay representing rapid progress. No multicollinearity was found among every variable. In addition, 40.38% patients carried ALS-related gene variants. The proportion with gene mutations in the within 1 year group was higher than that in the over 1 year group (p＜0.01). Furthermore, SETX was the most frequently mutated gene in this cohort (16.67%) including 4 uncertain mutation. Conclusion: Pregnancy and fertility were not associated with disease progression. Diagnostic delay was correlated with disease progression in this cohort. In addition, SETX might be a gene of concern for ALS patients of childbearing age.